Pengaruh Gradasi Dan Bentuk Butiran Pasir Terhadap Kuat Gesernya - Simanjuntak, Lambok Jadiaman; Yusa, Muhamad; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Gradation and grain shape of sand are some of the factors that influence the shear strength of sand. This needs to be considered, so that the effect can be maximized for construction related to sand. The purpose of this research is to find out how to analyzethe shape of the sand grains and analyze the behavior of the angle of friction (ϕ) due to the influence of the grading and shape of the grains. The test is carried out by dividingthe gradation, which consists of three variations with a relative density of 70%. Gradation 1 is dominated by medium granules as much a 100%, gradation 2 is dominated by coarse granules as much a 60%, and gradation 3 is dominated by finegranules as much a 60%. The shape of the sand grains is divided into two forms, namely the group of angular and rounded grains, which are distinguished based on themorphological parameters of the granules namely roundness (R), sphericity (S) and regularity (ρ). The morphological parameters of the granules are analyzed usingimageJ. The results showed that the analysis of grains shape of sand using imageJ, obtained levels of grain shape from the two sands, namely sub-angular and subrounded.The effect of gradation on angle of friction (ϕ) is gradation dominated bycoarse grains of 60%, namely gradation variation 2, and which has a long grain distribution, namely gradation variation 3 has a higher angle of friction (ϕ) compared to gradation variation 1. Comparison of the angle of friction (ϕ) between the grainshape of sand, that is sand with a sub-angular shape has a higher the angle of friction (ϕ) compared to sand with a sub-rounded shape.Keywords: Sand, gradation, particle shape, imageJ, roundness (R), sphericity (S), regularity (ρ), angle of friction (ϕ).